2018
DOI: 10.1186/s10397-017-1032-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristic and intraoperative findings of uterine perforation patients in using of intrauterine devices (IUDs)

Abstract: BackgroundIntrauterine devices (IUDs) are the most popular form of contraception used worldwide; however, IUD is not risk-free. IUD migrations, especially uterine perforations, were frequently occurred in patients. The aim of this study was to investigate the clinical characteristics and intraoperative findings in patients with migrated IUDs.Results29 cases of uterine perforation associated with migrated IUDs and 69 control patients were followed between January 2008 to March 2015. Patients who used IUDs withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 32 publications
0
27
0
1
Order By: Relevance
“…Perforations are reported to be mostly located in the myometrium and the greater omentum, with a frequency of 21%. In the second place, the colon sigmoid with a frequency of 17% and the left uterosacral ligament and bladder with a 10% frequency (5). Risk factors for perforation include IUD insertion during lactation, first time using the IUD, insertion during the first 6 months of postpartum, and anatomic abnormalities, such as cervical stenosis and a retroverted uterus (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Perforations are reported to be mostly located in the myometrium and the greater omentum, with a frequency of 21%. In the second place, the colon sigmoid with a frequency of 17% and the left uterosacral ligament and bladder with a 10% frequency (5). Risk factors for perforation include IUD insertion during lactation, first time using the IUD, insertion during the first 6 months of postpartum, and anatomic abnormalities, such as cervical stenosis and a retroverted uterus (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Perforations are reported to be mostly located in the myometrium and the greater omentum, with a frequency of 21%. In the second place, the colon sigmoid with a frequency of 17% and the left uterosacral ligament and bladder with a 10% frequency [5].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for perforation include IUD insertion during lactation, rst time using the IUD, insertion during the rst 6 months of postpartum, and anatomic abnormalities, such as cervical stenosis and a retroverted uterus [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] Risk factors that impact the occurrence of uterine perforation include breastfeeding and postpartum state, experience of the inserting doctor and uterine anatomy. [ 5 , 14 16 ] Women who were breastfeeding at the time of insertion have a 6-fold higher perforation risk than women who were not breastfeeding. [ 5 ] Malpositioned IUDs may lead to a high rate of pregnancy due to the possible reduced efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that the type of IUD did not affect the risk of uterine perforation, although stainless steel IUDs were less effective for contraception and easier to expulse. [ 5 , 14 ] As the incidence of IUD malposition is increased in patients with uterine structure abnormality, [ 16 ] it was not clear whether the partial septate uterus in this patient contributed to the IUD translocation.…”
Section: Discussionmentioning
confidence: 99%